SDSim: A generalized user friendly web ABM system to simulate spatiotemporal distribution of species under environmental scenarios. (January 2022) - Bioco, João; Cánovas, Fernando; Prata, Paula; Fazendeiro, Paulo
Abstract: This paper presents the Agent-Based Modelling System of spatial distribution of species SDSim . SDSim is an agent-based modelling system designed to simulate spatial distribution of species and populations for conservation and management purposes. SDSim gives to modellers the ability to simulate movements and colonization patterns of species given locations under study and a set of eco-geographical variables in which species depends on. Highlights: A new generic modelling tool tailored for ecological studies is offered. The proliferation and species' responses to environmental changes can be tracked. An easy to use ABM web interface was developed aiming at a worldwide availability.